Fluorescence lifetime imaging of AMPA receptor endocytosis in living neurons: effects of Aβ and PP1 - Prinkey, Katie; Thompson, Emily; Saikia, Junmi; Cid, Tania; Dore, Kim (Frontiers in Molecular Neuroscience, 2024)
The relative amount of AMPA receptors expressed at the surface of neurons can be measured using superecliptic pHluorin (SEP) labeling at their N-terminus. However, the high signal variability resulting from protein overexpression in neurons and the low signal observed in intracellular vesicles make quantitative characterization of receptor trafficking difficult. Here, we establish a real-time live-cell assay of AMPAR trafficking based on fluorescence lifetime imaging (FLIM), which allows for simultaneous visualization of both surface and intracellular receptors. Using this assay, we found that elevating amyloid-beta (Aβ) levels leads to a strong increase in intracellular GluA1 and GluA2-containing receptors, indicating that Aβ triggers the endocytosis of these AMPARs. In APP/PS1 Alzheimer's disease model mouse neurons, FLIM revealed strikingly different AMPAR trafficking properties for GluA1- and GluA3-containing receptors, suggesting that chronic Aβ exposure triggered the loss of both surface and intracellular GluA3-containing receptors. Interestingly, overexpression of protein phosphatase 1 (PP1) also resulted in GluA1 endocytosis as well as depressed synaptic transmission, confirming the important role of phosphorylation in regulating AMPAR trafficking. This new approach allows for the quantitative measurement of extracellular pH, small changes in receptor trafficking, as well as simultaneous measurement of surface and internalized AMPARs in living neurons, and could therefore be applied to several different studies in the future.